If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(1) = 1(1) + 3 Reorder the terms for easier multiplication: 1f = 1(1) + 3 Multiply 1 * 1 1f = 1 + 3 Combine like terms: 1 + 3 = 4 1f = 4 Solving 1f = 4 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by '1'. f = 4 Simplifying f = 4
| vw+uw=uv | | 2x+(x+6)=54 | | -2a-6a=24 | | (w^2-4w+7)+(3w^2+5w-3)= | | 2y-36x=45-38y | | 1350=45x+30y | | 10=8-4y | | 3x*ln(x+3)+4=0 | | 11w+2(3w-1)=5 | | (9y-6)(1.5)+3.5y= | | 3.50x+40=57.50 | | 7n+n=64 | | 30x^2-25x=0 | | 2(2x+3)=24 | | -2c-24=2c-12 | | 9u-5u=36 | | 5x+2=-5 | | 6-3x=14x+2 | | 13=7r-6-2 | | 8p-6(1-2p)=86 | | x+(x+2)=116 | | n+4.1n+6=-1.5(n+4.8) | | -3(4x-8)=2-4(3x-7) | | -16x^2+64x-26=0 | | 3x-8=-24 | | 8p-6(1-2b)=86 | | a+220=x-2(x+5)2 | | 8=2-5r-4 | | 38-1.7x=25+2.1x | | 3-1+(14-2)= | | -16x^2+64x-20=0 | | 5n-7=2n+14 |